PREVALENCE OF TRICHURIS SPP. INFECTION IN BALI CATTLE IN DUKUH SARI FARMING GROUP, PEMPATAN VILLAGE, RENDANG SUB-DISTRICT, KARANGASEM REGENCY OF BALI - Sihombing, Rio Fadly; Oka, Ida Bagus Made; Arjana, Anak Agung Gde (Buletin Veteriner Udayana, 2022)
This study aims to determine the prevalence of Trichuris spp. worm infection in Bali cattle and whether the relation of sex, age, and number of cows in the cage to the prevalence of Trichuris spp. worm infection in the Dukuh Sari cattle group, Pempatan village, Rendang sub-district, Karangasem district. The samples used were 102 Bali faeces and examined using floating concentration method, identification of worm eggs based on morphology and morphometry. The results of the examination found 6 samples (5.9%) positively infected with worms Trichuris spp. After statistical analysis through chi-square test, differences in age, sex, and number of cows in the cage did not affect the infection of Trichuris spp.